Expert system for selection of saving products using the backward chaining method at PT. State saving bank (persero) tbk. Pekanbaru branch office - Rian Ordila; Hendry Fonda; Hasti Rizki (Journal of Telecommunication Control and Intelligent System, 2021)
Bank is a business entity engaged in finance, especially providing services in payment traffic and money circulation. Each bank has savings products with their respective advantages. Prospective customers who want to save definitely want quality and profitable savings. PT. Bank Tabungan Negara (Persero) Tbk. Pekanbaru Branch Office is one of the banks that has many deposit products. There are several factors that influence the decision of prospective customers in choosing a deposit product, such as administrative fees, interest offered, minimum balance, and ease of transacting through e-channel services. A web-based expert system can be a solution to these problems because it has the same functions and knowledge as someone who must have, experience, to solve a problem and make decisions. The method used in this system is backward chaining. The basis of knowledge that contains facts and rules from this research is the name of the product and the criteria for the deposit product. This system uses the PHP programming language and uses a MySQL database as data storage. This system begins by asking several questions, analyzing customer needs according to the criteria for the deposit product and providing output product according to customer needs. With this system, it can make it easier for customers to determine what savings product choices are suitable for their needs and help BTN KC Pekanbaru customer service to make the account.